Solar seawater desalination photo-thermal material and preparation method and application thereof

By using the method of frozen dryness, calcium ions cross -linking and hydrophobic treatment in the diluted material of water gel solar seawater, solve the problem of complex and low evaporation efficiency of existing materials, and prepare the performance of high -efficiency light thermal conversion performance and good scalability The solar seawater fades the light and heat materials.

CN119350656APending Publication Date: 2025-01-24NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202411473897.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing hydrogel solar seawater desalination materials have complex preparation, low evaporation efficiency and poor scalability, which limit their application in actual seawater desalination.

Method used

By mixing polyethylene, sodium algina, solvents, and MXENE decentralized liquids for freezing and drying, a mxene/PVA/SA hydrogel is formed. Then perform hydrophobic treatment to prepare solar seawater with the Janus structure to fade the light and heat materials.

Benefits of technology

A simple, scalable, green and safe solar seawater desalination photothermal material has been realized. It has stable performance, good photothermal conversion performance, fast evaporation rate and high evaporation efficiency, and is suitable for large-scale industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350656A_ABST
    Figure CN119350656A_ABST
Patent Text Reader

Abstract

The invention provides a solar seawater desalination photo-thermal material and a preparation method and application thereof, and belongs to the field of seawater desalination. The hydrogel is obtained by crosslinking polyvinyl alcohol and sodium alginate, and MXene is used as a hydrogel photo-thermal conversion layer, so that the photo-thermal conversion capability and evaporation efficiency of the hydrogel are improved; the hydrogel is subjected to secondary cross-linking treatment by using calcium ions, the hydrogel and sodium alginate can form a chelate bond and an egg box structure, a hole framework can be further strengthened, the formed second cross-linked structure has good rigidity and can serve as a framework in a tent, and the second cross-linked structure and the formed second cross-linked structure are matched with each other, so that the pore space in the photo-thermal material can be stably maintained; in order to improve the desalination efficiency, a hydrophobic agent is used for forming a hydrophobic layer on the surface of the hydrogel, and excessive accumulation of salt in a photo-thermal material in a long-time evaporation process can be avoided through precise hydrophilic and hydrophobic regulation and control, so that excellent and stable photo-thermal conversion capability is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of seawater desalination, and in particular to a solar seawater desalination photothermal material and a preparation method and application thereof. Background Art

[0002] Water resources are a widely distributed natural resource on the earth. However, 97.5% of these water resources are salt water in seawater (average salinity is 35‰). If they are not treated, they cannot be directly used as drinking water, and cannot even be used for agricultural irrigation or industrial production. Solar interfacial water evaporation technology can simultaneously use two extremely abundant and easily accessible resources on the earth (seawater and solar energy) to produce clean water. It has become one of the effective ways to solve the problems of water shortage and increasingly serious water pollution. Compared with traditional seawater desalination technology, solar interfacial water evaporation technology has low cost requirements for materials and equipment, is environmentally friendly, has no secondary pollution and other by-products, and does not require the consumption of fossil fuels or the use of chemicals. It has become one of the most promising seawater desalination technologies and a very promising zero-carbon emission project.

[0003] Hydrogels have three-dimensional cross-linked polymer networks. Due to their good hydrophilicity and porous structure, hydrogels can absorb and transport water, making them ideal for high-performance solar desalination. MXene-doped hydrogels can absorb solar energy more efficiently and improve solar energy conversion efficiency. In most of the studies reported so far, hydrogel solar evaporators can meet good mechanical properties, water evaporation and other properties. However, the preparation method of hydrogels has problems such as complex preparation, low evaporation efficiency and poor scalability, which limits their application in actual seawater desalination.

[0004] Polyvinyl alcohol (PVA) and sodium alginate (SA) are widely used in seawater desalination due to their low cost, biocompatibility and hydrophilicity. Freeze drying and repeated freeze-thaw cycles are common methods for preparing PVA hydrogels. However, the PVA cross-linked network structure formed by these two physical cross-linking methods is too soft to support space, similar to the role of tarpaulin in tents, and can only initially maintain the directional pore structure formed by liquid nitrogen freezing. In addition, the poor photothermal conversion ability of PVA and SA prevents them from being directly used for evaporation. Even after being doped with MXene, their photothermal conversion performance will be greatly affected. Therefore, how to improve the structural stability and photothermal conversion performance of polyvinyl alcohol hydrogels has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] The purpose of the present invention is to provide a solar desalination thermal material and a preparation method and application thereof. The preparation method provided by the present invention has the characteristics of simple preparation, scalability, greenness and safety. The prepared solar desalination thermal material has stable performance, good photothermal conversion performance, fast evaporation rate and high evaporation efficiency.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a solar desalination photothermal material, comprising the following steps:

[0008] (1) polyvinyl alcohol, sodium alginate, solvent and MXene dispersion are mixed, and then freeze-dried to obtain MXene / PVA / SA hydrogel;

[0009] (2) cross-linking the MXene / PVA / SA hydrogel obtained in step (1) using a calcium ion solution to obtain an anisotropic MXene / PVA / SA hydrogel;

[0010] (3) The anisotropic MXene / PVA / SA hydrogel obtained in step (2) is subjected to hydrophobic treatment to obtain a solar desalination thermal material.

[0011] Preferably, in step (1), the mass ratio of polyvinyl alcohol to sodium alginate is 1:(1-3).

[0012] Preferably, the concentration of the MXene dispersion in step (1) is 5 to 10 mg / mL; and the ratio of the mass of the polyvinyl alcohol to the volume of the MXene dispersion is (1 to 3) g: (3 to 7) mL.

[0013] Preferably, the calcium ion solution in step (2) is a calcium chloride solution or a calcium sulfate solution.

[0014] Preferably, when the calcium ion solution is a calcium chloride solution, the cross-linking treatment is performed by dripping a calcium chloride solution on the surface of the MXene / PVA / SA hydrogel to obtain a black hydrogel, and then immersing it in distilled water to obtain an anisotropic MXene / PVA / SA hydrogel.

[0015] Preferably, the concentration of the calcium chloride solution is 10-20 mg / mL; the ratio of the mass of calcium chloride in the calcium chloride solution to the mass of sodium alginate in step (1) is (1-5):(2-3).

[0016] Preferably, when the calcium ion solution is a calcium sulfate solution, the cross-linking treatment is performed by immersing the MXene / PVA / SA hydrogel in the calcium sulfate solution for a cross-linking reaction, and then impregnating it with distilled water to obtain an anisotropic MXene / PVA / SA hydrogel.

[0017] Preferably, the hydrophobic treatment in step (3) is to immerse the surface of the light-to-heat conversion layer of the anisotropic MXene / PVA / SA hydrogel into a hydrophobic agent for hydrophobic treatment; the hydrophobic agent is any one of a polyvinylidene fluoride solution, a polyolefin solution and a polydimethylsiloxane solution.

[0018] The present invention provides a solar desalination photothermal material prepared by the preparation method described in the above technical solution, wherein the solar desalination photothermal material has a Janus structure.

[0019] The present invention provides the application of the solar seawater desalination photothermal material described in the above technical solution in solar seawater desalination.

[0020] The present invention provides a method for preparing a solar desalination photothermal material, comprising the following steps:

[0021] (1) polyvinyl alcohol, sodium alginate, a solvent and a MXene dispersion are mixed, and then freeze-dried to obtain a MXene / PVA / SA hydrogel; (2) the MXene / PVA / SA hydrogel obtained in step (1) is cross-linked with a calcium ion solution to obtain an anisotropic MXene / PVA / SA hydrogel; (3) the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is hydrophobicized to obtain a solar desalination thermal material. The present invention uses polyvinyl alcohol and sodium alginate to synthesize hydrogel by composite cross-linking, and uses MXene with a photothermal conversion efficiency of up to 97.7% as the hydrogel photothermal conversion layer to improve the photothermal conversion ability and evaporation efficiency of the hydrogel, and then forms an anisotropic hydrogel through freeze-drying; the hydrogel is cross-linked by using a calcium ion solution. Since sodium alginate has a special macromolecular structure, it can form a chelate bond with calcium ions to form a unique "egg-box structure", which can further strengthen the pore skeleton. The formed second cross-linked structure has good rigidity and can serve as the skeleton in the "tent". The two cooperate with each other to stably maintain the pore space in the photothermal material; in order to improve the desalination efficiency, a hydrophobic agent is used to form a hydrophobic layer on the surface of the hydrogel (i.e., the photothermal conversion layer), and the precise regulation of hydrophilicity and hydrophobicity can avoid the transitional accumulation of salt in the photothermal material during long-term evaporation, thereby achieving excellent and stable photothermal conversion ability.

[0022] The preparation method provided by the present invention has the characteristics of simple preparation, scalability, green and safe, etc. The prepared solar desalination photothermal material has stable performance, good photothermal conversion performance, fast evaporation rate and high evaporation efficiency, and is suitable for large-scale industrial promotion. The results of the embodiment show that the solar desalination photothermal material provided by the present invention has a Janus structure, a thickness of 2 to 20 mm, an evaporation rate of 1.2 to 3.5 kg / (m 2 h), the evaporation time is 1 to 12 h / day. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A process flow chart of the preparation of the solar desalination photothermal material provided by the present invention;

[0024] Figure 2 This is a physical picture of the solar desalination photothermal material prepared in Example 2;

[0025] Figure 3 The evaporation rate of the solar desalination photothermal material prepared in Examples 1 to 3;

[0026] Figure 4 This is a real picture of the generation and dissolution of salt crystals during the desalination process of the solar desalination thermal material prepared in Example 2 during a long-term simulated seawater evaporation test. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a solar desalination photothermal material, comprising the following steps:

[0028] (1) polyvinyl alcohol, sodium alginate, solvent and MXene dispersion are mixed, and then freeze-dried to obtain MXene / PVA / SA hydrogel;

[0029] (2) cross-linking the MXene / PVA / SA hydrogel obtained in step (1) using a calcium ion solution to obtain an anisotropic MXene / PVA / SA hydrogel;

[0030] (3) The anisotropic MXene / PVA / SA hydrogel obtained in step (2) is subjected to hydrophobic treatment to obtain a solar desalination thermal material.

[0031] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.

[0032] The present invention mixes polyvinyl alcohol, sodium alginate, a solvent and a MXene dispersion, and then freeze-dries the mixture to obtain a MXene / PVA / SA hydrogel.

[0033] In the present invention, the mass ratio of polyvinyl alcohol to sodium alginate is preferably 1:(1-3). The present invention controls the amount of polyvinyl alcohol and sodium alginate to form a cross-linked network with a stable structure during the freeze-drying process, thereby improving the structural stability of the hydrogel.

[0034] As an embodiment, the mass ratio of the polyvinyl alcohol to sodium alginate can be 1:1, 1:1.5, 1:2, 1:2.5 or 1:3.

[0035] In the present invention, the solvent is preferably water, more preferably deionized water. In the present invention, the ratio of the mass of the polyvinyl alcohol to the volume of the solvent is preferably (1-3) g: (3-8) mL, more preferably (1.6-3) g: (4-7) mL, and further preferably (2-2.4) g: (5-6) mL. By controlling the amount of the solvent, the present invention can ensure that the polyvinyl alcohol and sodium alginate maintain a suitable concentration in the solvent, thereby facilitating the cross-linking of the two.

[0036] In the present invention, the concentration of the MXene dispersion is preferably 5 to 10 mg / mL. In the present invention, the ratio of the mass of the polyvinyl alcohol to the volume of the MXene dispersion is preferably (1 to 3) g: (3 to 7) mL, more preferably (1.6 to 3) g: (4 to 6) mL, and further preferably (2 to 2.4) g: (5 to 6) mL. The present invention adds a MXene dispersion, MXene is a new type of two-dimensional material with a graphene-like structure, composed of transition metal carbides, nitrides or carbonitrides, which can ensure that the hydrogel has good photothermal conversion performance.

[0037] As an embodiment, the concentration of the MXene dispersion may be 5 mg / mL, 6 mg / mL, 7 mg / mL, 8 mg / mL, 9 mg / mL or 10 mg / mL.

[0038] In the present invention, the polyvinyl alcohol, sodium alginate, solvent and MXene dispersion are preferably mixed in the following manner: polyvinyl alcohol and sodium alginate are first added to the solvent and stirred to obtain a first mixed solution, and then the MXene dispersion is added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. In the present invention, the stirring and mixing temperature is preferably 80 to 100°C, more preferably 90°C; the stirring and mixing time is preferably 3 to 5h, more preferably 4h. The present invention does not have any special limitation on the stirring rate of the stirring and mixing, which can be determined according to the technical common sense of those skilled in the art to avoid splashing of the solution.

[0039] In the present invention, the freeze-drying method is preferably: first freezing the mixed MXene / PVA / SA hydrogel solution, and then freeze-drying to obtain a MXene / PVA / SA hydrogel.

[0040] In the present invention, the freezing method is preferably refrigerator freezing, freeze dryer freezing or liquid nitrogen freezing.

[0041] In the present invention, when the freezing method is refrigerator freezing or freeze dryer freezing, the number of freeze-thaw cycles is preferably 5 to 12 times, more preferably 8 to 10 times; the single freezing time is preferably 3 to 6 hours, more preferably 4 to 5 hours; the single thawing time is preferably 0.5 to 3 hours, more preferably 1 to 2.5 hours, and further preferably 1.5 to 2 hours.

[0042] In the present invention, when the freezing method is liquid nitrogen freezing, the liquid nitrogen freezing time is preferably 0.2 to 15 minutes, more preferably 5 to 10 minutes.

[0043] In the present invention, the freeze drying time is preferably 10 to 15 hours, more preferably 12 hours. In the present invention, the freeze drying is preferably carried out in a freeze dryer. The present invention has no particular limitation on the specific model of the freeze dryer, and a commercial product well known to those skilled in the art can be used. The present invention can remove free water and form an anisotropic hydrogel through freeze drying.

[0044] After obtaining the MXene / PVA / SA hydrogel, the present invention uses a calcium ion solution to cross-link the MXene / PVA / SA hydrogel to obtain an anisotropic MXene / PVA / SA hydrogel.

[0045] In the present invention, the calcium ion solution is preferably a calcium chloride solution or a calcium sulfate solution.

[0046] In the present invention, when the calcium ion solution is a calcium chloride solution, the cross-linking treatment method is preferably: adding a calcium chloride solution to the surface of the MXene / PVA / SA hydrogel to obtain a black hydrogel, and then immersing it in distilled water to obtain an anisotropic MXene / PVA / SA hydrogel.

[0047] In the present invention, the concentration of the calcium chloride solution is preferably 10-20 mg / mL; the ratio of the mass of calcium chloride to the mass of sodium alginate in the calcium chloride solution is preferably (1-5):(2-3). The present invention can ensure that calcium chloride and the hydrogel fully undergo cross-linking reaction by controlling the concentration of the calcium chloride solution and the amount of calcium chloride, thereby making the hydrogel fully anisotropic.

[0048] As an embodiment, the concentration of the calcium chloride solution can be 10 mg / mL, 12 mg / mL, 15 mg / mL, 18 mg / mL or 20 mg / mL; the ratio of the mass of calcium chloride to the mass of sodium alginate in the calcium chloride solution can be 1:2, 1:3, 2:2, 2:3, 3:2, 3:3, 4:2, 4:3, 5:2 or 5:3.

[0049] The present invention has no particular limitation on the dripping rate of the calcium chloride solution, and the solution can be slowly dripped according to the technical common sense of those skilled in the art. In the present invention, calcium chloride releases calcium ions at a relatively fast rate, and needs to be dripped gradually to make it uniformly cross-linked.

[0050] In the present invention, when the calcium ion solution is a calcium sulfate solution, the cross-linking treatment method is preferably: immersing the MXene / PVA / SA hydrogel in a calcium sulfate solution for a cross-linking reaction, and then impregnating it with distilled water to obtain an anisotropic MXene / PVA / SA hydrogel.

[0051] In the present invention, the calcium sulfate solution is preferably a saturated calcium sulfate solution; the cross-linking reaction time is preferably 8 to 10 hours, more preferably 8 to 9 hours. In the present invention, the calcium ion rate of the calcium sulfate solution is slow, so the cross-linking reaction time is controlled after all immersion to ensure that the calcium ions are fully cross-linked with the hydrogel.

[0052] The present invention adopts a calcium ion solution to cross-link the hydrogel. Since sodium alginate SA has a special macromolecular structure, it can form a chelate bond with calcium ions to form a unique "egg-box structure", which can further strengthen the pore skeleton. The formed second cross-linked structure has good rigidity and can serve as the skeleton in the "tent". The two cooperate with each other to stably maintain the pore space in the photothermal material.

[0053] The present invention has no special limitation on the specific operation of the distilled water immersion, and the operation can be performed according to the technical common sense of those skilled in the art to remove impurities. The present invention can remove impurities in the hydrogel by distilled water immersion, thereby preventing these impurities from affecting the photothermal conversion ability of the hydrogel.

[0054] After obtaining the anisotropic MXene / PVA / SA hydrogel, the present invention performs hydrophobic treatment on the anisotropic MXene / PVA / SA hydrogel to obtain a solar desalination photothermal material.

[0055] In the present invention, the hydrophobic treatment is preferably performed by immersing the surface of the light-to-heat conversion layer of the anisotropic MXene / PVA / SA hydrogel into a hydrophobic agent for hydrophobic treatment.

[0056] In the present invention, the hydrophobic agent is preferably any one of polyvinylidene fluoride (PVDF) solution, polyolefin solution and polydimethylsiloxane (PDMS) solution, more preferably polydimethylsiloxane solution; the solvent in the hydrophobic agent is preferably an organic solvent, more preferably n-hexane analytical grade solvent.

[0057] In the present invention, when the hydrophobic agent is a polydimethylsiloxane solution, the concentration of the polydimethylsiloxane solution is preferably 0.24-2.4wt%, more preferably 0.5-2wt%, and further preferably 1-1.5wt%. The present invention has no particular limitation on the specific source of the polydimethylsiloxane solution, and a commercial solution well known to those skilled in the art can be used.

[0058] As an embodiment, the hydrophobic agent is preferably prepared by mixing polydimethylsiloxane of model DC184 of Sylgard Dow Corning brand and a solvent according to different concentrations.

[0059] The present invention has no particular limitation on the specific amount of the hydrophobic agent, as long as the surface of the light-to-heat conversion layer of the anisotropic MXene / PVA / SA hydrogel can be completely immersed in the hydrophobic agent.

[0060] In the present invention, the time of the hydrophobic treatment is preferably 1 to 20 minutes, more preferably 2 to 15 minutes, and further preferably 5 to 12 minutes. The present invention uses the above-mentioned hydrophobic agent to perform hydrophobic treatment on the hydrogel. After the organic solvent evaporates, the solute will form a hydrophobic film on the surface of the material, which can significantly improve its hydrophobicity, so that the solar desalination photothermal material can use sunlight to desalinate seawater in a self-floating form.

[0061] After the hydrophobic treatment is completed, the present invention preferably sequentially subjects the hydrophobic treated hydrogel to standing at room temperature and soaking to remove impurities, thereby obtaining a solar desalination photothermal material.

[0062] In the present invention, the standing time at room temperature is preferably 12 to 48 hours, more preferably 24 to 36 hours.

[0063] In the present invention, the soaking and impurity removal is preferably soaking in deionized water. The present invention can remove unreacted chemical substances and reduce the influence of impurities on the photothermal conversion ability of the hydrogel by soaking in deionized water.

[0064] The preparation process flow chart of the solar desalination photothermal material provided by the present invention is as follows: Figure 1 As shown. Figure 1 It can be seen that after polyvinyl alcohol and sodium alginate are mixed in a solvent, a MXene dispersion is added, and liquid nitrogen freezing, freeze drying, calcium ion cross-linking and surface hydrophobic treatment are performed in sequence to obtain the solar desalination photothermal material required by the present invention.

[0065] The present invention uses polyvinyl alcohol and sodium alginate to synthesize hydrogel by composite cross-linking, uses MXene with a photothermal conversion efficiency of up to 97.7% as the hydrogel photothermal conversion layer, controls the pore size of the hydrogel by adjusting the concentration ratio of the materials, and improves the photothermal conversion capacity and evaporation efficiency of the hydrogel; cross-links the hydrogel using a calcium ion solution, and because sodium alginate SA has a special macromolecular structure, it can form a chelate bond with calcium ions to form a unique "egg-box structure", which can further strengthen the pore skeleton, and the formed second cross-linked structure has good rigidity and can serve as a skeleton in the "tent". The two cooperate with each other to stably maintain the pore space in the photothermal material; in order to improve the desalination efficiency, PDMS is used to form a hydrophobic layer on the surface of the hydrogel (i.e., the photothermal conversion layer), and the precise regulation of hydrophilicity and hydrophobicity can avoid the transitional accumulation of salt in the photothermal material during long-term evaporation, thereby achieving excellent and stable photothermal conversion capacity.

[0066] The preparation method provided by the present invention has the characteristics of simple preparation, scalability, greenness and safety. The prepared hydrogel has stable performance, good photothermal conversion performance, fast evaporation rate and high evaporation efficiency, and is suitable for large-scale industrial promotion.

[0067] The present invention also provides a solar desalination photothermal material prepared by the preparation method described in the above technical solution.

[0068] In the present invention, the thickness of the solar desalination photothermal material is preferably 2 to 20 mm, more preferably 5 to 15 mm, and further preferably 8 to 12 mm.

[0069] In the present invention, the solar desalination photothermal material preferably has a Janus structure.

[0070] In the present invention, the evaporation time of the solar desalination photothermal material is preferably 1 to 12 h / day, more preferably 3 to 9 h / day.

[0071] The PVA / SA composite hydrogel prepared by the present invention has good mechanical properties and stability. Using MXene as a photothermal conversion material can greatly enhance the photothermal conversion capacity of the photothermal material. In addition, precise hydrophilic and hydrophobic regulation in the photothermal conversion layer can prevent salt crystals from accumulating and clogging in the photothermal material, maintain the excellent light absorption and water transport capacity of the hydrogel, and thus achieve excellent and stable desalination performance.

[0072] The present invention also provides application of the solar seawater desalination photothermal material described in the above technical solution in solar seawater desalination.

[0073] The present invention has no special limitation on the specific application of the solar desalination photothermal material in solar desalination, and any application method familiar to those skilled in the art may be used.

[0074] As an implementation mode, the solar desalination thermal material can be self-floating to desalinate seawater using sunlight.

[0075] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0076] Example 1

[0077] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0078] (1) First, 0.16 g of polyvinyl alcohol and 0.24 g of sodium alginate were added to 4 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 4 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen by liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 12 h to obtain a MXene / PVA / SA hydrogel;

[0079] (2) adding 8 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0080] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a hydrophobic agent for hydrophobic treatment for 2 minutes, wherein the hydrophobic agent is a mixture of polydimethylsiloxane and a solvent, wherein the polydimethylsiloxane is a polydimethylsiloxane of the Sylgard Dow Corning brand DC184 model, and the solvent is an analytical pure solvent of n-hexane. The concentration of the hydrophobic agent is 2 wt %, and then the sample is taken out and allowed to stand at room temperature for 24 hours, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material, which is recorded as sample one.

[0081] Example 2

[0082] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0083] (1) First, 0.2 g of polyvinyl alcohol and 0.3 g of sodium alginate were added to 5 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 5 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen with liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 12 h to obtain a MXene / PVA / SA hydrogel;

[0084] (2) adding 10 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0085] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a hydrophobic agent for hydrophobic treatment for 2 minutes, wherein the hydrophobic agent is a mixture of polydimethylsiloxane and a solvent, wherein the polydimethylsiloxane is a polydimethylsiloxane of the Sylgard Dow Corning brand DC184 model, and the solvent is an analytical pure solvent of n-hexane. The concentration of the hydrophobic agent is 2 wt %, and then the sample is taken out and allowed to stand at room temperature for 24 hours, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material, which is recorded as sample 2.

[0086] The actual picture of the solar desalination photothermal material prepared in Example 2 is as follows Figure 2 As shown. Figure 2 It can be seen that the solar desalination photothermal material prepared by the preparation method provided by the present invention has a stable structure and good skeleton support.

[0087] Example 3

[0088] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0089] (1) First, 0.24 g of polyvinyl alcohol and 0.36 g of sodium alginate were added to 6 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 6 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen with liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 12 h to obtain a MXene / PVA / SA hydrogel;

[0090] (2) adding 12 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0091] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a hydrophobic agent for hydrophobic treatment for 2 minutes, wherein the hydrophobic agent is a mixture of polydimethylsiloxane and a solvent, wherein the polydimethylsiloxane is a polydimethylsiloxane of the Sylgard Dow Corning brand DC184 model, and the solvent is an analytical pure solvent of n-hexane. The concentration of the hydrophobic agent is 2 wt %, and then the sample is taken out and allowed to stand at room temperature for 24 hours, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material, which is recorded as sample three.

[0092] The thickness of the solar desalination photothermal materials prepared in Examples 1 to 3 was measured, and the thickness of the hydrogels of Samples 1 to 3 were 8 mm, 10 mm, and 12 mm, respectively.

[0093] The evaporation rate of the solar desalination photothermal materials prepared in Examples 1 to 3 was tested, and the results were as follows: Figure 3 As shown in Table 1, Figure 3 The curve of the simulated salt water in is the evaporation rate without adding solar desalination thermal materials:

[0094] Table 1 Evaporation rate of solar desalination photothermal materials prepared in Examples 1 to 3

[0095] Example Evaporation time (min) <![CDATA[Evaporation rate (kgm -2 h -1 )]]> Example 1 45 2.02 Example 2 45 3.15 Example 3 45 2.85

[0096] The test method for the evaporation rate (Δv) is as follows: use a beaker as a container for simulated salt water (3.5wt%), place a piece of light-proof tin foil on the beaker, there is a hole in the middle of the tin foil, and place samples one to three in the hole respectively. Due to the porosity of solar desalination thermal materials, the thermal materials can be suspended on the surface of the simulated salt water. Under indoor conditions of room temperature of 25°C and humidity of 60%, a sunlight-simulated xenon lamp is used as the light source, and a full-spectrum optical power meter is used to adjust the light intensity of the sunlight-simulated xenon lamp to 1kW·m -2 , and irradiated vertically on the surface of samples one to three, and an electronic balance was used to record the mass change of the simulated salt water in real time;

[0097] The calculation formula of evaporation rate (Δv) is shown in Formula I:

[0098] Δv=m / (A·t) Formula I

[0099] In formula I, m is the mass change of water during the test; A is the vertical projection area of ​​the sample surface; and t is the evaporation time.

[0100] From Table 1 and Figure 3 It can be seen that the evaporation rate of the solar desalination photothermal material prepared in Example 2 is the best, which is 3.15 kg / (m 2 h). The photothermal material can quickly heat up by 10°C within 5 minutes, has good photothermal conversion capability, and reaches 37°C after 15 minutes. The photothermal material has low thermal conductivity, which prevents heat from being transferred back to the water below, which is conducive to thermal management.

[0101] The above analysis results show that by adjusting the mass of the components, the thickness of the hydrogel can be controlled and the evaporation rate and evaporation performance of the evaporation material can be improved.

[0102] The solar desalination photothermal material prepared in Example 2 was subjected to a long-term simulated seawater evaporation test, and the results obtained are as follows: Figure 4 As shown. Figure 4 It can be seen that when the solar intensity is 1kW / m 2 The illumination time is 10h, and the evaporation rate of solar desalination photothermal material is 2.80kg / (m 2 h), and salt accumulation can be avoided in this process, indicating that the solar desalination photothermal material provided by the present invention has a promoting effect on avoiding salt accumulation and accelerating water evaporation.

[0103] Example 4

[0104] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0105] (1) First, 0.2 g of polyvinyl alcohol and 0.3 g of sodium alginate were added to 5 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 5 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen with liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 12 h to obtain a MXene / PVA / SA hydrogel;

[0106] (2) adding 10 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0107] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a hydrophobic agent for hydrophobic treatment for 2 minutes, wherein the hydrophobic agent is a mixture of polydimethylsiloxane and a solvent, wherein the polydimethylsiloxane is a polydimethylsiloxane of the Sylgard Dow Corning brand DC184 model, and the solvent is an analytical pure solvent of n-hexane. The concentration of the hydrophobic agent is 2 wt %, and then the hydrophobic agent is taken out and allowed to stand at room temperature for 24 hours, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material.

[0108] The thickness of the solar desalination photothermal material prepared in Example 4 is about 10 mm, and the evaporation rate is 2.45 kg / (m 2 h).

[0109] Example 5

[0110] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0111] (1) First, 0.2 g of polyvinyl alcohol and 0.3 g of sodium alginate were added to 5 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 5 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen with liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 12 h to obtain a MXene / PVA / SA hydrogel;

[0112] (2) adding 10 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0113] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a 2 wt% polydimethylsiloxane solution (the solvent of the polydimethylsiloxane solution is an analytical grade n-hexane solvent) for hydrophobic treatment for 2 min, then taken out and allowed to stand at room temperature for 24 h, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material.

[0114] The thickness of the solar desalination photothermal material prepared in Example 5 is about 10 mm, and the evaporation rate is 1.60 kg / (m 2 h).

[0115] Example 6

[0116] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0117] (1) First, 0.2 g of polyvinyl alcohol and 0.3 g of sodium alginate were added to 5 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 5 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen with liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 12 h to obtain a MXene / PVA / SA hydrogel;

[0118] (2) adding 10 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0119] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a hydrophobic agent for hydrophobic treatment for 2 minutes, wherein the hydrophobic agent is a mixture of polydimethylsiloxane and a solvent, wherein the polydimethylsiloxane is a polydimethylsiloxane of the Sylgard Dow Corning brand DC184 model, and the solvent is an analytical pure solvent of n-hexane. The concentration of the hydrophobic agent is 2 wt %, and then the hydrophobic agent is taken out and allowed to stand at room temperature for 24 hours, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material.

[0120] The thickness of the solar desalination photothermal material prepared in Example 6 is about 10 mm, and the evaporation rate is 1.23 kg / (m 2 h).

[0121] By comparing Example 2 with Examples 4 to 6, it can be seen that when other conditions remain unchanged, as the hydrophobic treatment time increases, the thickness of the obtained solar desalination thermal material remains basically unchanged, while the evaporation rate shows a trend of first increasing and then decreasing, indicating that the hydrophobic treatment time can affect the evaporation rate of the solar desalination thermal material, and when the hydrophobic treatment time is 2 minutes, the evaporation rate of the solar desalination thermal material is optimal.

[0122] Example 7

[0123] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0124] (1) First, 0.2 g of polyvinyl alcohol and 0.3 g of sodium alginate were added to 5 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 5 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen by liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 10 h to obtain a MXene / PVA / SA hydrogel;

[0125] (2) adding 10 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0126] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a hydrophobic agent for hydrophobic treatment for 2 minutes, wherein the hydrophobic agent is a mixture of polydimethylsiloxane and a solvent, wherein the polydimethylsiloxane is a polydimethylsiloxane of the Sylgard Dow Corning brand DC184 model, and the solvent is an analytical pure solvent of n-hexane. The concentration of the hydrophobic agent is 2 wt %, and then the hydrophobic agent is taken out and allowed to stand at room temperature for 24 hours, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material.

[0127] The thickness of the solar desalination photothermal material prepared in Example 7 is about 9 mm, and the evaporation rate is 2.12 kg / (m 2 h).

[0128] Example 8

[0129] A method for preparing a solar desalination photothermal material, comprising the following steps:

[0130] (1) First, 0.2 g of polyvinyl alcohol and 0.3 g of sodium alginate were added to 5 mL of water, stirred at 90 ° C for 4 h to obtain a first mixed solution, and then 5 mL of a 6 mg / mL MXene dispersion was added to the first mixed solution, and mixed evenly to obtain a mixed MXene / PVA / SA hydrogel solution. Finally, the mixed MXene / PVA / SA hydrogel solution was frozen with liquid nitrogen for 5 min, and then placed in a freeze dryer for freeze drying for 15 h to obtain a MXene / PVA / SA hydrogel;

[0131] (2) adding 10 mL of a 15 mg / mL calcium chloride solution to the surface of the MXene / PVA / SA hydrogel obtained in step (1) to obtain a black hydrogel, and then immersing the hydrogel in distilled water to remove impurities to obtain an anisotropic MXene / PVA / SA hydrogel;

[0132] (3) The surface of the photothermal conversion layer of the anisotropic MXene / PVA / SA hydrogel obtained in step (2) is immersed in a hydrophobic agent for hydrophobic treatment for 2 minutes, wherein the hydrophobic agent is a mixture of polydimethylsiloxane and a solvent, wherein the polydimethylsiloxane is a polydimethylsiloxane of the Sylgard Dow Corning brand DC184 model, and the solvent is an analytical pure solvent of n-hexane. The concentration of the hydrophobic agent is 2 wt %, and then the hydrophobic agent is taken out and allowed to stand at room temperature for 24 hours, and finally immersed in deionized water to remove impurities and unreacted chemicals to obtain a solar desalination photothermal material.

[0133] The thickness of the solar desalination photothermal material prepared in Example 8 is about 10 mm, and the evaporation rate is 2.64 kg / (m 2h).

[0134] By comparing Example 2 with Examples 7 to 8, it can be seen that when other conditions remain unchanged, as the freeze-drying time increases, the thickness of the obtained solar desalination thermal material first increases slightly and then remains unchanged, while the evaporation rate shows a trend of first increasing and then decreasing. Analysis shows that when the freeze-drying time is short, the free water is not completely sublimated, and a small amount remains, while when the freeze-drying time is long, the structure of the thermal material is slightly affected, so the evaporation rate is affected. Therefore, when the freeze-drying time is 12h, the evaporation rate of the solar desalination thermal material is optimal.

[0135] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a solar desalination photothermal material, comprising the following steps: (1) polyvinyl alcohol, sodium alginate, solvent and MXene dispersion are mixed, and then freeze-dried to obtain MXene / PVA / SA hydrogel; (2) cross-linking the MXene / PVA / SA hydrogel obtained in step (1) using a calcium ion solution to obtain an anisotropic MXene / PVA / SA hydrogel; (3) The anisotropic MXene / PVA / SA hydrogel obtained in step (2) is subjected to hydrophobic treatment to obtain a solar desalination thermal material.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of polyvinyl alcohol to sodium alginate is 1:(1-3).

3. The preparation method according to claim 1, characterized in that: The concentration of the MXene dispersion in step (1) is 5 to 10 mg / mL; the ratio of the mass of the polyvinyl alcohol to the volume of the MXene dispersion is (1 to 3) g: (3 to 7) mL.

4. The preparation method according to claim 1, characterized in that: The calcium ion solution in step (2) is a calcium chloride solution or a calcium sulfate solution.

5. The preparation method according to claim 4, characterized in that: When the calcium ion solution is a calcium chloride solution, the cross-linking treatment is performed by dripping the calcium chloride solution on the surface of the MXene / PVA / SA hydrogel to obtain a black hydrogel, and then immersing it in distilled water to obtain an anisotropic MXene / PVA / SA hydrogel.

6. The preparation method according to claim 4, characterized in that: The concentration of the calcium chloride solution is 10-20 mg / mL; the ratio of the mass of calcium chloride in the calcium chloride solution to the mass of sodium alginate in step (1) is (1-5):(2-3).

7. The preparation method according to claim 4, characterized in that: When the calcium ion solution is a calcium sulfate solution, the cross-linking treatment is performed by immersing the MXene / PVA / SA hydrogel in the calcium sulfate solution for a cross-linking reaction, and then impregnating it with distilled water to obtain an anisotropic MXene / PVA / SA hydrogel.

8. The preparation method according to claim 1, characterized in that: The hydrophobic treatment in step (3) is to immerse the surface of the light-to-heat conversion layer of the anisotropic MXene / PVA / SA hydrogel into a hydrophobic agent for hydrophobic treatment; the hydrophobic agent is any one of a polyvinylidene fluoride solution, a polyolefin solution and a polydimethylsiloxane solution.

9. The solar desalination photothermal material prepared by the preparation method according to any one of claims 1 to 8, wherein the solar desalination photothermal material has a Janus structure.

10. Use of the solar desalination photothermal material according to claim 9 in solar desalination.

Citation Information

Patent Citations

  • Preparation method of interface photo-thermal evaporator with hydrophobic, salt-resistant, hydrophilic and oil-resistant characteristics

    CN117902662A

  • MXene precipitate / polyvinyl alcohol / sodium alginate composite aerogel three-dimensional evaporator and preparation method thereof

    CN117920075A

  • Photo-thermal conversion body, preparation method and interface evaporation device

    CN118420031A

Cited By

  • Evaporation material for high-concentration brine treatment and power generation based on ion regulation and preparation method

    CN122277989A